If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27.15 + 15 = X Combine like terms: 27.15 + 15 = 42.15 42.15 = X Solving 42.15 = X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 42.15 + -1X = X + -1X Combine like terms: X + -1X = 0 42.15 + -1X = 0 Add '-42.15' to each side of the equation. 42.15 + -42.15 + -1X = 0 + -42.15 Combine like terms: 42.15 + -42.15 = 0.00 0.00 + -1X = 0 + -42.15 -1X = 0 + -42.15 Combine like terms: 0 + -42.15 = -42.15 -1X = -42.15 Divide each side by '-1'. X = 42.15 Simplifying X = 42.15
| 6x+3-7x=6 | | y/-2=11 | | -3(3p+3)-2(3-14p)=3(9+6p) | | tan^2(x)-1/343 | | 13-16=5y+6-4y | | -6x+3(-x+14)=141 | | 12x+2=4x-6 | | 4(x+1.2)=3x+9.7 | | 175=7(-5x-5) | | 122=69xT | | 10log(30/10^-12) | | 1-1/64x^4=0 | | 1-1/64x^4 | | -2x+4a=6 | | (-19)(7/11) | | 3(2x-1)+2=19 | | 29+34-28+(36-2)= | | 5x-7x-9x=-19 | | 3/2b-1/3 | | w=2.5+15t | | bg-5=1243 | | x+(x*.22)=583 | | (3x-7x-6)+(-3x+2)= | | 3x-5=7x-8 | | 4y+20x=4 | | v=9(5)-11 | | 3(7)+1=z | | b=18(13-11) | | u=4(19-9) | | (3c^3d^3/28b^5)/(12c^2d/7ab^3) | | s=14(3)-19 | | y+7=-(x-2) |